Bioresorbable shape-adaptive structures for ultrasonic monitoring of deep-tissue homeostasis - Liu, Jiaqi; Liu, Naijia; Xu, Yameng; Wu, Mingzheng; Zhang, Haohui; Wang, Yue; Yan, Ying; Hill, Angela; Song, Ruihao; Xu, Zijie; Park, Minsu; Wu, Yunyun; et al. (Science (American Association for the Advancement of Science), 2024)
Monitoring homeostasis is an essential aspect of obtaining pathophysiological insights for treating patients. Accurate, timely assessments of homeostatic dysregulation in deep tissues typically require expensive imaging techniques or invasive biopsies. We introduce a bioresorbable shape-adaptive materials structure that enables real-time monitoring of deep-tissue homeostasis using conventional ultrasound instruments. Collections of small bioresorbable metal disks distributed within thin, pH-responsive hydrogels, deployed by surgical implantation or syringe injection, allow ultrasound-based measurements of spatiotemporal changes in pH for early assessments of anastomotic leaks after gastrointestinal surgeries, and their bioresorption after a recovery period eliminates the need for surgical extraction. Demonstrations in small and large animal models illustrate capabilities in monitoring leakage from the small intestine, the stomach, and the pancreas.